p53 in renal cell carcinoma: a biomarker for disease progression - Habib, Manal A.; Ibrahim, Mazin J.; Farhan, Saad D. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: P53 is an important tumor marker in many malignancies, the P53 gene is a tumor suppressor gene that plays a key role in the regulation of the cell cycle.